Energy Savings Opportunity Survey, Fort McPherson, Georgia. Volume I. - EMC ENGINEERS INC MARIETTA GA (1992)
The purpose of the study was to analyze energy requirements and energy conservation opportunities (ECOs) for selected buildings at Fort McPherson, Georgia. The study analyzes energy requirements and energy conservation opportunities (ECOs) for selected buildings at Fort McPherson, Georgia. ECOs EVALUATED The 17 ECO projects identified in the SOW to be evaluated for selected buildings. During the entrance interview conference, ECO 18 was included. ECO 18, which converts incandescent exit sign light bulbs to fluorescent bulbs, was evaluated for all buildings specified for ECO 15, lighting controls. Based on discussions with DEH, it was also decided to include the results of previous lighting studies which were originally evaluated as shared energy savings projects. The results are included as ECO 19; economics are based on design, bid, and construction, direct by the Government, rather than by an energy service contractor under a shared energy savings contract. Subsequent to the field survey, each ECO for each building was reviewed to determine if it was technically feasible. ECOs which are not technically feasible were eliminated from further evaluation. A complete list of these ECOs, and the reasons they were eliminated, are included in Table ES-2 on page ES-3. In addition, as the facilities were surveyed, some ECOs included in the SOW were found to apply to buildings not identified in the ECO matrix (Annexes B and C). With the approval of DEH, these buildings were added to the original list.